Exploring the West - Yasuda, Anita (Exploring America's regions., 2018)
Examines the climate, history, famous natural and manmade landmarks, plant and animal life, industries, and peoples and cultures of the contemporary American West. Includes primary sources, a facts section, critical thinking questions, color photographs and maps, a glossary, and online resources.